2.85-kW cryogenic Nd:YAG slab laser operating at 946 nm - Chang, Jin-Quan; Bian, Qi; Bo, Yong; Shen, Yu; Peng, Qin-Jun (Frontiers in Physics, 2023)
A several-kilowatt level diode-pumped Nd:YAG slab laser at 946 nm is demonstrated with the cryogenically‑cooled system. By measuring the absorption spectra of 0.6 at.% Nd:YAG crystal at room and cryogenic temperature, the absorption line width at 808 nm is a little narrowed and a little wavelength blue shift is also observed with the cooling temperature decreasing from 300 to 77 K. The measured thermal conductivity increases from 10 to 70 W/mˑK, and the thermal expansion coefficient decreases from 7.5*10-6 to 1.5*10-6/K, which would give a guide for simulating temperature gradient and thermal induced stress distributions in the crystal slab. With a compact cavity of homemade cryogenically cooled Nd:YAG crystal slab, the oscillator realizes the record of output power of 2.85 kW. The pulse repetition rate and pulse width of laser are 400 Hz and 200 μs, respectively, and the center wavelength under the full power is 946.2 nm with a bandwidth of about 0.5 nm.